Aerobic energy turnover and exercise economy profile during race simulation in a world-record-breaking male full-distance triathlete - Christensen, P. M. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To investigate metabolism and exercise economy during prolonged race simulation (>4 h) in a world-class, full-distance triathlete to help guide/adjust strategies for training, nutrition, hydration, and thermoregulation.